Impact of service delivery on sustainable local development (LED) in Greater Tubatse Municipality, Limpopo Province - Thobejane, Jerry Ngwetjane (University of Limpopo (Turfloop Campus), 2011)
The poverty and unemployment that face the Greater Tubatse Municipality (GTM) despite being endowed with mineral resources prompted me to undertake a study to unearth possible challenges. This sub-region of the Greater Sekhukhune District Municipality, which is one of the five municipalities, looks better off as compared to other local municipalities within the district. Suffice it to say that it is one of the most poverty stricken, even worse than the Fetakgomo Local Municipality in the west. This local municipality is rich in mineral deposits and is a booming industrial hub of the Limpopo Province. Given the potential the municipality has, it is regrettable to realise that the residents of the municipality are the most poorest and unemployed. Like each and every municipality, GTM has a fully-fledged economic (LED) and land development department under which Local Economic Development falls. This brings confusion as to whether the municipality is facing human or financial constraints in terms of fulfilling its LED role. That brings us to the aim of the study, namely, the intention to investigate the impact service delivery, coupled with infrastructure development, could produce on sustainable LED. Thus, the present researcher decided to consider a qualitative approach/methodology towards this problem as a way to investigate the underlying circumstances that could hinder the realization and flourishing of LED within the municipality. The reason being to collect first-hand information in terms of what is transpiring in the municipality. On one hand there is a lack of the above-mentioned resources, on the other hand, leadership within the municipality should be reviewed. As a recommendation, the GTM should focus on areas that could bring incentives and confidence to the investors by providing sustainable infrastructure, a crime free environment and thus position the municipality as a tourism destination, these are some of the aspects that could grow an LED. The aspect of skills within the municipality, particularly in the area of LED, should be beefed up as part of the recruitment strategy. LED is concerned with the creation of an environment that will engage stakeholders in implementing strategies and programmes.
Thesis (M.Dev.) --University of Limpopo, 2011
Keywords: Service delivery; Sustainable development; 338.968; Job creation -- South Africa; Unemployment; Economic development -- South Africa -- Limpopo